Features of Hyundai Kona electric diagnostics using the LAUNCH X-431 PRO 3S multi-brand scanner - Hnatov, A.; Ulianets, О.; Ivanov, V.; Arhun, S.; Гнатов, Андрій Вікторович; Аргун, Щасяна Валіковна; Ульянець, Ольга Анатоліївна; Іванов, Владислав Вячеславович (Харківський національний автомобільно-дорожній університет, 2025)
The rapid growth of the electric vehicle fleet in Ukraine has created a practical need for reliable diagnostic methods that are compatible with locally available service equipment. In particular, service stations must be able to assess the technical condition of popular models such as the Hyundai Kona Electric using universal, multi-brand diagnostic tools. Goal. The aim of this paper is to investigate the capabilities and limitations of the LAUNCH X-431 PRO 3S multi-brand diagnostic scanner for technical diagnosis of the Hyundai Kona Electric, with a focus on battery condition, key electronic control units (ECUs) and the detection of hidden faults and data manipulations. Methodology. The study combines a literature review on EV diagnostics, OBD-II–based approaches and battery health assessment with practical experiments on a Hyundai Kona Electric using the LAUNCH X-431 PRO 3S. A step-by-step diagnostic algorithm is proposed, and real-time data streams are analyzed for a range of ECUs, including Airbag, IC (cluster module), IBU-BCM, Smart Key Unit, EV Battery System and OBC. Results. The experiments show that the LAUNCH X-431 PRO 3S provides full access to the main EV subsystems, enabling rapid fault code reading, detailed analysis of live parameters and execution of special functions. The paper demonstrates how the combined analysis of battery voltages, accumulated energy, operating time and AC charging counters can be used to infer realistic mileage, identify odometer tampering and evaluate high-voltage battery state of health. Originality. The work offers one of the first structured diagnostic procedures for Hyundai Kona Electric using a broadly available multi-brand scanner, linking specific X-431 data parameters with EV-specific diagnostic tasks such as verifying real mileage, assessing battery degradation and detecting intentional masking of warning indicators. Practical value. The proposed algorithm and parameter interpretations provide service engineers and used-EV evaluators with a practical, reproducible approach to comprehensive diagnostics of Hyundai Kona Electric using LAUNCH X-431 PRO 3S, reducing diagnostic time, improving fault detection accuracy and lowering the risks associated with purchasing and servicing used EVs.
Особливості діагностики Hyundai Kona electric з використання мультимарочного сканеру LAUNCH X-431 PRO 3S
Keywords: electric vehicle diagnostics; OBD-II; battery condition; real-time monitoring; LAUNCH X-431; error codes; energy consumption; діагностика електромобілів; стан акумулятора; моніторинг у режимі реального часу; коди помилок; споживання енергії; 629.331; 10.30977/AT.2219-8342.2025.57.0.02